2017
DOI: 10.1021/acs.langmuir.7b02445
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Nanoscale Roughness to Anomalous Colloid Retention and Stability Behavior

Abstract: All natural surfaces exhibit nanoscale roughness (NR) and chemical heterogeneity (CH) to some extent. Expressions were developed to determine the mean interaction energy between a colloid and a solid-water interface, as well as for colloid-colloid interactions, when both surfaces contain binary NR and CH. The influence of heterogeneity type, roughness parameters, solution ionic strength (IS), mean zeta potential, and colloid size on predicted interaction energy profiles was then investigated. The role of CH wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
95
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(99 citation statements)
references
References 54 publications
4
95
0
Order By: Relevance
“…Similar stabilization behavior has been reported for other macromolecules including polaxamers and poloxamines 290 [42,43,44], poly(ethylene glycol) (PEG) [48], and methoxy poly(ethylene glycol) (mPEG) [49,50]. This stability enhancement resulting from macromolecule adsorption is commonly attributed to electrosteric repulsion, though a recent study by Bradford et al [51] found that nanoscale roughness could also explain this behavior. This result is a key advantage for use in environmental systems 295 where the ionic content of natural waters can lead to aggregation and therefore modified transport characteristics.…”
supporting
confidence: 64%
“…Similar stabilization behavior has been reported for other macromolecules including polaxamers and poloxamines 290 [42,43,44], poly(ethylene glycol) (PEG) [48], and methoxy poly(ethylene glycol) (mPEG) [49,50]. This stability enhancement resulting from macromolecule adsorption is commonly attributed to electrosteric repulsion, though a recent study by Bradford et al [51] found that nanoscale roughness could also explain this behavior. This result is a key advantage for use in environmental systems 295 where the ionic content of natural waters can lead to aggregation and therefore modified transport characteristics.…”
supporting
confidence: 64%
“…The presence of some forms of hydrophobic organic matter in the solution (Table S1) and the sediment surface may enhance the hydrophobic interaction between the partially hydrophobic viruses (PRD1 and MS2), which lead to their higher retention. In addition, nanoscale chemical and especially physical heterogeneity on the surfaces of colloids are known to strongly influence their adhesive interaction (Attinti et al, 2010;Bradford et al, 2017). The viral protein coat may contain weakly acidic and basic amino acid groups which act as localized positive and negative charges (Gerba, 1984) and it has a span of hydrophobic amino acids which will determine the hydrophobicity of viruses (Bendersky and Davis, 2011;Bradford and Torkzaban, 2012;Shen, et al, 2012d).…”
Section: Virus Retention Under Various Physicochemical Conditionsmentioning
confidence: 99%
“…Natural solid surfaces like sand grains always contain a wide distribution of physical (e.g., roughness) or chemical (e.g., metal oxides) heterogeneities (Bhattacharjee et al, 1998;Shen et al, 2012c). Previous studies have demonstrated that roughness height and fraction, and positive zeta potential and fraction, at a specific location on the collector (sand) surface can significantly reduce the magnitude of the energy barrier to attachment and the depth of the primary minimum for viruses (Bradford et al, 2017;Torkzaban, 2013, 2015;Sasidharan et al, 2017b;Torkzaban and Bradford, 2016). In contrast to smooth latex nanoparticles, the virus exhibits chemical (e.g., lipid membrane and protein coat) (Meder et al, 2013) and physical heterogeneity (e.g., spikes and tail) (Huiskonen et al, 2007;Kazumori, 1981) on their surface.…”
Section: Mathematical Modeling Of Virus Retentionmentioning
confidence: 99%
“…This could be explained by the difference in adhesive strength of the viruses at a specific attachment location. Previous studies demonstrated that the presence of nanoscale roughness and chemical heterogeneity on sand (Han et al, 2016; Choo et al, 2015) and virus (Kazumori, 1981; McKenna et al, 1992; Merckel et al, 2005; Peralta et al, 2013) are expected to reduce the magnitude of the energy barrier to attachment/detachment and the depth of the primary minimum (Bradford et al, 2017; Bradford and Torkzaban, 2013, 2015; Torkzaban and Bradford, 2016). The observation of low rates of virus detachment (Table 1) is consistent with slow, diffusion‐controlled, virus release from a primary minimum with a low probability of release (e.g., the energy barrier to detachment of 5 to 10 kT) (Bradford et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…For example, irreversible virus attachment may occur at smooth surfaces with chemical heterogeneity due to the presence of deep primary minimum, whereas reversible virus interaction was expected on rough surfaces due to the presence of a shallow primary minimum (Bradford et al, 2017; Bradford and Torkzaban, 2012). This implies that only a very small fraction of the solid surface may contribute to irreversible virus attachment in a deep primary minimum since nanoscale roughness is ubiquitous on solid and virus surfaces (Bradford et al, 2017; Bradford and Torkzaban, 2015). These findings are consistent with the small values of α (0.028 – 0.081) and S f (8.5 × 10 −7 –7.8 × 10 −9 ) shown in Table 1, and the observed blocking behavior for both viruses in the BTCs (Fig.…”
Section: Resultsmentioning
confidence: 99%